The Ricker Hills Tillite provides evidence of Oligocene warm-based glaciation in Victoria Land, Antarctica - BARONI, CARLO; SALVATORE, MARIA CRISTINA; FASANO F; GIORGETTI G; RIBECAI C. (Global and Planetary Change, 2008)
The relationship between the Ricker Hills Tillite (RHT), which represents the northernmost outcrop of lithified continental glacial deposits in Victoria Land, is discussed with respect to the glacial landscape assemblage of the Ricker Hills, a nunatak at the internal border of the Transantarctic Mountains. A warm-based ice sheet deposited the tillite and induced syn- to post-depositional glacial deformation under wet conditions both of the tillite and of the bedrock. The thickness of the ice sheet on the nunatak is estimated to have been 600 m, at most. The area had been deeply eroded before deposition of the RHT as documented by the low elevation of tillite outcrops located in overdeepened depressions of the nunatak. Micropaleontological analysis evidences only the presence of Permian to Jurassic palynomorphs. X-ray diffraction and SEM–EDS analyses of clay minerals in the RHT indicate continental chemical weathering under wet conditions after the RHT deposition. As documented by clay mineral assemblage variation in CRP drillholes, the progressive cooling of the Antarctic continent allowed chemical weathering in “warm” conditions until the Late Oligocene period in southern Victoria Land, leading to a chronological constrain for RHT deposition. Conservatively estimating the sea level to have been between the tillite outcrops and the erosional trimline limiting horns in the Ricker Hills, at the time of RHT deposition, we suggest that the maximum uplift of the area would not have exceeded 900–1500 m since at least Late Oligocene.